2015
DOI: 10.1111/hpb.12491
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic strategy and timing of intervention in infected necrotizing pancreatitis: an international expert survey and case vignette study

Abstract: Background: The optimal diagnostic strategy and timing of intervention in infected necrotizing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…There is no consensus on the timing of PCD in the stepup approach. A significant variation in the timing of PCD could be observed among the reports by different centers [16], ranging from 9 to 55 days after the onset of symptoms [5]. Sugimoto et al have shown that PCD can achieve better outcomes if proactively performed in the early stages of necrotizing pancreatitis before the development of severe sepsis [17].…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on the timing of PCD in the stepup approach. A significant variation in the timing of PCD could be observed among the reports by different centers [16], ranging from 9 to 55 days after the onset of symptoms [5]. Sugimoto et al have shown that PCD can achieve better outcomes if proactively performed in the early stages of necrotizing pancreatitis before the development of severe sepsis [17].…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of FNA aspiration and culture has become less favourable due to a 20-25% false negative rate, potentially as a result of the timing of the FNA as well as prior antibiotic usage (14). International experts agree that currently there is no consensus on the role of FNA and therefore it is not used routinely (44). For example, a stable patient with a positive FNA can potentially be treated with antibiotics alone and conversely patients with a high level of clinical suspicion and/or organ failure with a negative FNA will progress to further surgical intervention.…”
Section: Diagnosis Of Infectionmentioning
confidence: 99%
“…Current literature shows that 35-64% of patients with INP can be treated with delayed catheter drainage, without the need for invasive necrosectomy [9,13]. In a recent international survey, although not evidence based, 45% of expert pancreatologists proclaimed that they immediately proceed with catheter drainage once infected pancreatic necrosis has been established [12]. Indeed, various case series suggest that encapsulation is not a ‘sine qua non' for catheter drainage to be successful [13].…”
Section: Treatment Of Infected Pancreatic Necrosismentioning
confidence: 99%
“…With the oral diet and on-demand tube feeding strategy, only approximately one third of patients required a nasojejunal feeding tube. It is difficult to speculate on factors that explain the observed differences with previous trials and observational studies, which suggested an improved outcome after early nasoenteric tube feeding as compared with total parenteral nutrition, other than study design and methodology [8,10,11,12,13] The timing of early nasoenteric tube feeding was similar to the timing mentioned in previous studies and similar criteria for enrolling patients at high risk for complications were used. One of the major issues with observational studies is that one cannot differentiate between cause and effect; for instance, less severely ill patients may have been fed earlier.…”
Section: Feeding In Pancreatitismentioning
confidence: 99%